VOCATIONAL AND PATRIOTIC EDUCATION OF STUDENTS OF DEFENSE SPECIALTIES AT A TECHNICAL UNIVERSITY - N. P. Ustinova (Obrazovanie i Nauka, 2016)
The aim of the publication is an experimental research of patriotic qualities of students – future engineers of the defense industry. Methods. The study is conducted with the use of system-based analysis methods, teacher modeling, observation, interviews, pedagogical testing, and questionnaires. Diagnosis and evaluation of personal qualities of students are carried out using morphological life values test (modified by I. G. Senin), and questionnaire «The need for achieving the goal» (modified by Y. M. Orlov). The reliability of the results is granted by the use of statistical processing of empirical methods. Results. The average empirical values have been obtained concerning the level of professional and patriotic education of students of defence specialties at technical universities. It has been shown that targeted educational activities carried out on the basis of the identified organizational and pedagogical conditions, contributes to the level of professional and patriotic education of students of defense specialties at a Technical University.Scientific novelty. In relation to students – future professionals of defense industry, the concept of «professional – patriotic education» is clarified, which appears to be an integrative quality of a person, including cognitive, emotion-andvalue component and rational-activity components. The organizational and pedagogical conditions of vocational patriotic education of students of defense specialties are identified; the conditions are united into two groups: the creation of professional-oriented educative environment and creating the opportunities for active participation of students in educational and professional activities. Practical significance. Designed criterion-evaluation units are used to evaluate the current level of professional and patriotic education of students. Identified set of organizational and pedagogical conditions has been implemented in the process of patriotic education of students of defense specialties at Izhevsk State Technical University named after M. T. Kalashnikov (Izhevsk), Tula State University (Tula), Kovrov State Technological Academy named after V. A. Degtjarjov (Kovrov), Ryazan Higher Airborne Command School named after V. F. Margelov (Ryazan).